Heat, Crime, and Punishment - Behrer, A. Patrick (World Bank, Washington, DC, 2022)
Using administrative criminal records from Texas, this paper shows how heat affects criminal defendants, police officers, prosecutors, and judges. It finds that arrests increase by up to 15 percent on hot days, driven by increases in violent crime. There is no evidence that charging-day heat impacts prosecutorial decisions. However, working alone, judges dismiss fewer cases, issue longer prison sentences, and levy higher fines when ruling on hot days. Higher incomes, newer housing, more teamwork, and less accessible weapons may decrease these adverse effects of heat. Even with adaptation, the paper forecasts that climate change will increase crime and have substantial distributional consequences.